Birthday bash! [videorecording (DVD)] (PBS, 2025)
Come celebrate the magic of birthdays with these festive tales from your favorite PBS Kids series! Alma hunts for the perfect gift for her great-grandmother's 100th birthday. Carl is given a universal screwdriver. Miss Elaina learns to appreciate gifts from friends. Pinkalicious has a pinkaperfect party. Chris and Martin make Aviva a porcupine quill necklace for her birthday. The Wombats make a boat-shaped birthday cake. And much more birthday fun!